Spiritual education in the special school setting for pupils with learning difficulties/disabilities - Baker, John (International journal of children's spirituality, 2012)
This article is based on empirical research into headteachers’/principals’ perception of the meaning of spiritual education and the provision they make and the strategies they use in order to meet the statutory requirement to promote the spiritual development of pupils/students through the curriculum in the special school setting for pupils with learning difficulties/disabilities in the UK. Arising out of the research, values (secular and religious, particularly Christian), relationships and pupils’ feelings and emotions are the three main attributes of spiritual education identified in terms of its meaning. Assemblies/acts of collective worship, religious education and personal, social and health education are aspects of the schools’ curricular provision most frequently mentioned by the headteachers. The strategies which the headteachers use to meet pupils’ special educational needs include ‘modelling’ the school’s values, particularly through close relationships; the use of alternative and augmentative communication systems and raising pupils’ awareness and wonder of the world through multi-sensory and other experiences.